POLA ASUH PEREMPUAN YANG BERSTATUS SINGLE PARENT PADA PENDIDIKAN ANAK (STUDI KASUS PEREMPUAN BERSTATUS SINGLE PARENT DI PASURUAN) - Muniro, Khoirun Nafidatul (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2009)
A family is as a basic means of education toward children’s growth process. In onther words, children education in family, basically, is an educational process of growth and competence as well as performance from birth. In this context, a family plays an important role as a significant basic education for an upcoming education system. However, how does a case of woman partially live as a single parent functioning her educational system? In this context, a writer does research on what Islamic concepts of a family education are. Empirically and methodologically, how are educational systems supposed to be developed in a family education?; And how is the influence of a woman-single parent’s educational system to her children based on gender perspective?